Phytochemical and antioxidant screening of Moringa oleifera for its utilization in the management of hepatic injury - Noor Younis; Muhammad Issa Khan; Tahir Zahoor; Muhammad Naeem Faisal (Frontiers in Nutrition, 2022)
IntroductionPhytochemicals present in Moringa oleifera (M. oleifera) leaves have performed several physiological functions in human system such as anticarcinogenic, antidiabetic, antioxidant, immunomodulatory, hepatoprotective and antiatherogenic functions.MethodsPhytochemical and antioxidant potential of M. oleifera leaves extracts were measured. Histopathology, biochemical analysis, and gene expression tests were performed on serum, blood, and liver in animal model.Results and discussionsThe toxic dose of N-acetyl-para-aminophenol (APAP) induced severe structural and functional changes in liver. Pre-treatment with M. oleifera ameliorated organ injury by normalizing the level of liver biomarkers and serum proteins. A low expression level of MAPK-8, TRAF-4, and TRAF-6 genes was observed in the M. oleifera treated group in comparison to positive control (hepatotoxic rats). M. oleifera leaves pretreatment amended APAP induced apoptosis and replenished hepatic cells. M. oleifera leaves extract as low-cost and sustainable treatment could be used in pharmaceutical industry for reducing hepatic degenerative changes in non-communicable diseases.